Curricular intervention increases adolescents’ knowledge about asthma: a randomized trial - Ana Carla C. Coelho; Carolina de Souza-Machado; Thiara S. de Oliveira; Tássia Natalie N. dos Santos; Álvaro A. Cruz; Adelmir Souza-Machado (Jornal de Pediatria, 2018)
Objectives: To evaluate the impact of a curricular intervention concerning the knowledge about asthma among adolescents from a public school. Methods: This was a randomized, controlled trial study on a curricular intervention in asthma, carried out with asthmatic and non-asthmatic adolescents. The study participants were divided into a curricular intervention group for asthma (IG), and a control group with traditional curriculum (CG). Topics related to asthma were included in the curriculum, such as the disease concept, triggering factors, treatment, symptoms, action plan, and beliefs in popular myths about the disease. These topics were evaluated through a questionnaire with scores ranging from 0 to 20 points, expressed by the mean score. The acquisition of knowledge was evaluated 90 days and 540 days after the start of the intervention (baseline), by applying the mixed linear model for analysis of associations. Results: 181 students participated in the study (IG = 101 and CG = 80). As shown by their scores before the intervention; the students were unaware about asthma (IG: x¯=10.7±2.9 vs. CG: x¯=11.5±2.7 points), its treatment (IG: x¯=1.6±0.9 vs. CG: x¯=1.6±0.8 points), and reported beliefs in popular myths about the disease (IG: x¯=1.5±1.1 vs. CG: x¯=1.7±1.1 points). After the intervention, the IG showed higher overall knowledge (GI: x¯=15.5±3.1 points), as well as knowledge about the treatment (GI: x¯=2.5±1.0 points), and two times more knowledge in the field “beliefs in popular myths about the disease” when compared to the CG. A greater probability of achieving satisfactory knowledge about asthma was noted in the IG (RR = 3.5), with NTT = 2.0. Conclusion: The inclusion of the asthma topic in the curriculum improved knowledge about the disease in a subgroup of students. Resumo: Objetivo: Avaliar o impacto de uma intervenção curricular sobre o conhecimento em asma dos adolescentes de um colégio público. Métodos: Ensaio controlado e randomizado de uma intervenção curricular em asma, conduzido com adolescentes, asmáticos e não asmáticos, alocados em: grupo intervenção curricular em asma (GI) e grupo controle com currículo tradicional (GC). Foram inseridos no currículo tópicos relacionados à asma tais como o conceito, fatores desencadeantes, tratamento, sintomas, plano de ação e crenças em mitos populares sobre a doença, avaliados por meio de um questionário com escore de 0-20, expressos em média de acertos. Avaliou-se a apreensão do conhecimento 90 dias e 540 dias após o início da intervenção (baseline), aplicou-se o modelo linear misto para análise das associações. Resultados: 181 estudantes participaram do estudo (GI = 101 e GC = 80). Os estudantes desconheciam a asma, como revelam os seus escores anteriores à intervenção (GI: x¯=10,7±2,9 vs. GC: x¯=11,5±2,7 acertos), seu tratamento (GI: x¯=1,6±0,9 vs. GC: x¯=1,6±0,8 acertos) e relataram crenças em mitos populares sobre a doença (GI: x¯=1,5±1,1 vs. GC: x¯=1,7±1,1 acertos). Após a intervenção, o GI apresentou maior conhecimento geral (GI: x¯=15,5±3,1 acertos); sobre o tratamento (GI: x¯=2,5±1,0 acertos) e duas vezes mais conhecimento no domínio “crenças em mitos populares sobre a doença” comparado ao GC. Maior probabilidade de alcançar conhecimento satisfatório sobre a asma foi observado no GI (RR = 3,5), com NNT = 2,0. Conclusão: A inserção do tema asma no currículo é capaz de elevar o conhecimento sobre a doença em um subgrupo de estudantes. Keywords: Asthma, Knowledge, Education, School health, Prevention and control, Palavras-chave: Asma, Conhecimento, Educação, Saúde escolar, Prevenção & controle